Effect of Arthrospira (Spirulina) maxima on Cadmium-Chloride-Induced Alterations in Sexual Behavior and Fertility in Male Wistar Rats - Galván-Colorado Candelaria; García-Rodríguez Rosa Virginia; Mojica-Villegas María Angélica; García-Martínez Yuliana; Cristóbal-Luna José Melesio; Chamorro-Cevallos Germán (MDPI AG, 2024)
Chronic exposure to potentially toxic elements (PTEs) such as cadmium (Cd) leads to male reproductive toxicity through the generation of oxidative stress. Spirulina Arthrospira maxima (AM) is a cyanobacterium that has been consumed since ancient times for its high nutritional value, and in recent years for its antiviral, hepatoprotective, hypoglycemic, anticancer, and antioxidant effects, among others. This study aimed to evaluate the effects of AM against the damage to reproductive health induced by Cd. A total of 48 10-week-old sexually experienced male Wistar rats were distributed in five groups (n = 8): control; vehicle (tween-water); cadmium chloride (CdCl2) 5 mg/kg; and three doses of AM (100, 200 and 400 mg/kg) + CdCl2 5 mg/kg. All treatments were orally administered once a day for 36 consecutive days. At the end, sexual behavior was evaluated, and semen, testicle, and blood samples were obtained to analyze sperm quality, enzymatic activity, and testosterone levels, respectively. Rats exposed to Cd showed a decrease in sexual behavior, as well as in the quality of reproductive health, and an increase in oxidative stress; while rats exposed simultaneously to AM + Cd showed an improvement in all this parameters. Based on our results, we believe that the mechanism by which AM exerts its effect could be attributed to the presence of phycobiliproteins. These compounds are responsible for exerting an antioxidant effect and chelating effect on elements such as Cd.